Anticorrosion Behaviour of Calcareous Deposits Formed on Steel Heat-Exchange Surfaces - Georgii Vasyliev; Svitlana Vasylieva (Advances in Materials Science and Engineering)
A new electrode to study both scaling and corrosion processes of mild steel in tap water was developed. Two identical steel rings are placed on the outside of a glass tube which is heated from inside with an electric spiral; the rings are connected to a corrometer to form a two-electrode corrosion probe. The corrosion rate variations with scale thickness, scale deposition time, and solution composition are measured using the linear polarization resistance technique. The deposited scale was formed of calcite crystals of 50–100 μm as established with SEM and XRD. The scale layer of 0.2 mm formed in tap water within 90 hours reduces the steel corrosion rate from 0.8 to 0.1 mm/year and serves as a barrier layer to prevent further corrosion.